Recruitment of minority students to U.S. epidemiology degree programs - George, Diane Marie M.St.; Schoenbach, Victor J.; Reynolds, Gladys H.; Nwangwu, John; Adams-Campbell, Lucile L. (Annals of Epidemiology, 1997)
PURPOSE: African-, Hispanic-, and Native Americans are underrepresented in the field of epidemiology including degree programs. As part of the assessment component of its mandate, the American College of Epidemiology Committee on Minority Affairs conducted a survey of minority recruitment activities of U.S. epidemiology degree programs. METHODS: The survey, containing questions related to marketing activities, institutional infrastructure, financial support, academic offerings, and receptive/supportive environment, was mailed to all programs identified in Episource as offering epidemiology degrees. Separate responses were requested concerning activities at the department and school levels. RESULTS: Fifty- two completed questionnaires were received (response rate of 79%). All but two institutions had at least one activity conducted by either the department or the school. However, all activities were more common at the school- than at the department-level. Indeed, some activities [a written minority student recruitment plan (6% of departments and 52% of schools), personnel with minority recruitment responsibilities (4% of departments and 73% of schools] were almost exclusively school-sponsored. Although marketing-type activities were the most common minority recruitment tool used by departments, only 21% made visits to minority schools, 17% visited other colleges specifically to recruit minorities, and 12% produced materials targeted to ethnic/racial minorities. Six percent of the departments and 19% of the schools offered financial support (grants, fellowships, scholarships) to almost all underrepresented minority students. CONCLUSIONS: Even though individual epidemiology degree programs may not see a need for general recruitment activities in order to maintain the size of their applicant pool, minority- specific recruitment activities should be undertaken to enhance and diversify that pool. We recommend that epidemiology departments develop, adopt, and implement comprehensive written plans for the recruitment of underrepresented minority students into their programs.
Keywords: Adult; Career Choice; Educational Measurement; Epidemiology; Fellowships and Scholarships; Female; Humans; Male; Minority Groups; Minority groups; Minority health; School Admission Criteria; Schools, Public Health; Schools- veterinary; Schools-public health; Student recruitment; United States; article; dept.pch; education program; epidemiology; human; minority group; priority journal; questionnaire; student; united states

The impact of the Yale faculty development program: Clinical alcohol and drug research and education (cadre) on medical student teaching about substance abuse - O'Connor, Patrick G.; Pearsall, H. Rowland; Ball, Samuel A.; Forsyth, Brian W. C.; Faraclas, William G.; Schottenfeld, Richard S. (Substance Abuse, 1997)
Increasing emphasis on the need for medical student education about substance abuse has led to the development of a variety of training efforts through faculty development. The Yale University School of Medicine Faculty Development Program or CADRE (Clinical Alcohol and Drug Research and Education) was instituted in 1992 for the purpose of enhancing substance abuse teaching in the Yale medical student curriculum. CADRE faculty were identify in internal medicine, pediatrics, and psychiatry. Prior to the program, there was limited formal teaching about substance abuse in the Yale curriculum and no coordinated effort across disciplines. The enhancement of teaching activities occurred primarily within four required “core”; clinical clerkships for third‐and fourth‐year medical students. Student evaluations of this new teaching activity were positive. The CADRE program was successful at developing a multidisciplinary core faculty group with expertise in substance abuse teaching and resulted in the development of a coordinated, multidisciplinary substance abuse curriculum for Yale medical students.
Keywords: Faculty development; Medical education; Substance abuse; article; clinical research; curriculum; dept.pch; education program; faculty development; medical education; medical student; substance abuse; teaching

New admission measure needed - Williams, AL; Gallup, P (Academic Medicine, 1997)
Keywords: Humans; School Admission Criteria; Schools, Medical; United States; dept.pch; education; human; letter; medical school

Homeless mentally ill veterans: race, service use, and treatment outcomes. - Rosenheck, Robert A; Leda, Catherine; Frisman, Linda K; Gallup, Peggy (American Journal of Orthopsychiatry, 1997)
Comparisons of service use and treatment outcomes for 145 black and 236 white homeless veterans with mental disorders showed few differences. A greater improvement in psychiatric symptoms and alcohol problems among white than black veterans did not hold true when black veterans had participated in the residential treatment component of the program. The implications of the findings for the successful treatment of homeless black veterans are discussed.
Keywords: Adult; African Americans; European Continental Ancestry Group; Female; Hispanic Americans; Homeless Persons; Humans; Male; Mental Disorders; Mental Health Services; Middle Aged; Residential Treatment; Veterans; article; cost effectiveness analysis; dept.pch; homelessness; mental disease; mental health service; outcomes research; race difference; residential care; soldier; treatment outcome